Investigation of publication trends and hot topics on onchocerciasis between 2000 and 2022 - Sevil Alkan; Esra Gürbüz; Selahattin Aydemir (Journal of Zoonotic Diseases, 2023)
This study aimed to use bibliometric tools to investigate onchocerciasis research conducted worldwide between 2000 and 2022. This bibliometric study was carried out using the Scopus database. The analysis unit was the documents conducted on onchocerciasis between 2000 and 2022. The data obtained after the last evaluations were transferred to VOSviewer (VOSviewer 1.6.19 for Microsoft Windows systems) and biblioshiny (bibliometrix R package) programs for analysis. The present results showed that 1026 documents on onchocerciasis were indexed in the Scopus database between 2000 and 2022. 2554 authors have published this literature, and the annual growth rate was 1.34 %. Forty-one articles were published in 2000, and after 2014, there was an increase in the number of articles. The most publications were published in 2018 (n = 82). PLOS Neglected Tropical Diseases (n = 97) and Parasites & Vectors (n = 46) published the most publications on onchocerciasis. Most of the publications were published by authors from the United States (n = 341), the United Kingdom (n = 228), Cameroon (n = 150), Nigeria (n = 132), and Germany (n = 120). The documents originating from the United States (n = 2372) had the highest citation numbers. The onchocerciasis research landscape between 2000 and 2022 is outlined in this report. Furthermore, the analysis offers an enhanced comprehension of the trends in onchocerciasis development over the previous 23 years, which might serve as a scientific benchmark for subsequent research.